2017
DOI: 10.1088/1757-899x/227/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations to evaluate the effects of cutting parameters on cutting temperature and residual stresses during milling process of the AISI 1045

Abstract: Abstract. Today major metal cutting companies in industrial countries, looking to gain time and reduce manufacturing costs while respecting the environment. There are many phenomena which affect the quality and production costs of the product, including cutting efforts, cutting temperature, residual stresses, etc. A better understanding of these phenomena will reduce production costs and maximize productivity. The aim of this work is to analyze the effect of machining conditions (cutting speed, feed speed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In another research, Abdul Karim et al [14], by investigating the effect of machining parameters on the thermal loads produced during the machining process of AISI 1045 steel, found that the temperature of the machining area increases mainly with the increase of cutting depth and speed. During the research of Ozel and colleagues [15] on AISI H13 steel, it was found that the small radius of the tip of the tool and the low hardness of the workpiece cause an increase in the roughness value. Using experimental tests and statistical analysis, Jadda et al [16] investigated the effect of cutting parameters in the process of cutting and found that cutting velocity and progress rate are two important factors in determining cutting force and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In another research, Abdul Karim et al [14], by investigating the effect of machining parameters on the thermal loads produced during the machining process of AISI 1045 steel, found that the temperature of the machining area increases mainly with the increase of cutting depth and speed. During the research of Ozel and colleagues [15] on AISI H13 steel, it was found that the small radius of the tip of the tool and the low hardness of the workpiece cause an increase in the roughness value. Using experimental tests and statistical analysis, Jadda et al [16] investigated the effect of cutting parameters in the process of cutting and found that cutting velocity and progress rate are two important factors in determining cutting force and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-related problems encountered in multiedge milling are dealt with, for instance, in [ 6 , 7 , 8 ]. Armendia et al examined how high cutting speeds in milling contributed to the tool wear.…”
Section: Introductionmentioning
confidence: 99%